Not hide from the truth: to skorynology without task orientation - Charota, Ivan A. (Journal of the Belarusian State University. Sociology, 2019)
Suggested is a generalized view of modern domestic Skorynology (Skoryna studies) that is habituated to a lot of open questions; among them are those that are of great importance for both describing the life and determining the foundations of the worldview of the East Slavic printer (name, religion, nearest environment, certain stages of life, etc.). It is shown that some of these issues are considered unreasonably as unsolvable, and some are hurriedly classed as finally solved. Attention is drawn to newly found handwritten materials, certifying that the life and activities of Skoryna are connected with the Moldovan lands and directly related to some historical personalities of Serbia.